Analysis of Intellectual Demands Embodied in The Learning Objectives Prescribed for Mathematics and Science Components of The Teacher Training Manual - Okanlawon, Ayoade Ejiwale (International Journal of Research in STEM Education, 2022)
Abstract Higher-order thinking is as an important skill needed to function effectively in 21st century classrooms. Consequently, teacher professional development should be geared towards assisting teachers in acquiring skills needed to plan intellectually demanding classroom activities for their students. Engaging teachers in activities such as inquiry-oriented discussion, investigation, experimentation with new classroom practices, expansion of pedagogical knowledge, and acquisition of new teaching skills and development of innovative approaches to teaching is an effective way of promoting higher-order cognitive skills. However, information about the quality of the teacher training manual in terms of its intellectual demands are lacking. Hence, the need for this study becomes imperative. Existing prescribed learning objectives for Mathematics and Science components of the manual which served as the data source were analyzed by using qualitative content analysis method. The findings showed that the majority of the learning objectives prescribed in the teacher training manual clustered around lower-order cognitive skills. In addition, reasonable proportion of learning objectives prescribed for the Mathematics component emphasized higher-order cognitive skills more than the Science component. Further results revealed that the subject-matter content is more intellectually demanding than the aspect of the manual focusing on pedagogical knowledge. These have implications for the prescription of learning objectives in teacher training manual and planning of high-quality teacher professional development programme.